2016
DOI: 10.1007/s11695-016-2399-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in Gut Microbiota After Gastric Bypass and Sleeve Gastrectomy Bariatric Surgery Vary According to Diabetes Remission

Abstract: Overall, RYGB produces greater and more predicted favourable changes in gut microbiota functional capacity than SG. An increase in Roseburia species was the only compositional change common to both types of surgery among those achieving diabetes remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
235
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(258 citation statements)
references
References 35 publications
11
235
1
11
Order By: Relevance
“…Murine model experiments indicate that the microbiome plays a critical role in weight gain following transient loss of obesity 218 . In accordance with this observation, recent human translational research showed consistent increase in the Roseburia genus in patients with successful resolution of diabetes following both RYGB and SG surgery 219 . Such microbiome changes associated with fecal metabolite alterations, may be relevant for modulating epigenetic mechanisms.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Murine model experiments indicate that the microbiome plays a critical role in weight gain following transient loss of obesity 218 . In accordance with this observation, recent human translational research showed consistent increase in the Roseburia genus in patients with successful resolution of diabetes following both RYGB and SG surgery 219 . Such microbiome changes associated with fecal metabolite alterations, may be relevant for modulating epigenetic mechanisms.…”
Section: Introductionsupporting
confidence: 79%
“…Vertical sleeve gastrectomy results in the resection of about 80% of the greater curvature portion of the stomach and causes a restriction of food intake, acceleration of gastric emptying and alteration of gut hormones affecting satiety and appetite. VSG was noted to produce only modest microbial changes compared to RYGB 219 but did lead an increase in the Bacteroidetes/Firmicutes ratio and a decrease in Eubacterium rectale, Ruminococcus obeum, Lachnospiraceae bacterium and F. prausnitzii (in those with impaired glucose tolerance only) 227 . VSG also led to an increase in malabsorption due to loss of energy-rich fatty acids in the stool, impaired bile acid circulation 227 and resulted in greater capacity for metabolism of amino acids 219 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA study in a stool sample of T2D who separately undergone laparoscopic Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) surgery revealed more Firmicutes and Actinobacteria phyla and lesser Bacteroidetes phyla in RYGB group; unlikely more Bacteroidetes phyla found in SG group; similar Roseburia species was noticed in both groups [36].…”
Section: Reason Iii: Diabetes Specific Gut Microbiotamentioning
confidence: 99%
“…A recent study 10 has compared changes in gut microbiome following both RYGB and sleeve gastrectomy (SG). At baseline (following a two-week weight reduction diet), no significant differences in gut microbiota composition was found.…”
mentioning
confidence: 99%